Updates on coronavirus (COVID-19) and kidney - Seyed Zanyar Athari; Daryoush Mohajeri; Mir Alireza Nourazar; Yousef Doustar (Society of Diabetic Nephropathy Prevention, 2020)
The severe acute respiratory syndrome (SARS) is an infectious disease developed in Wuhan, China, at first. It involves the respiratory system and other organs like kidney, gastrointestinal tract and nervous system as well. The recent reports indicated that renal disorder is prevalent in coronavirus patients. The aim of this study was to provide a review of nephropathy caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) and its mechanisms. The Web of Science, Scopus, and PubMed databases were systematically searched. Articles reporting nephropathy, coronavirus disease (COVID-19), coronavirus and the renal injury were included for assessment. Study designs, contrast agents, case reports and results were assessed. Of the assessed studies, suggested mechanisms include sepsis which caused cytokine storm syndrome or perhaps direct cellular injury due to the virus. In patients who were studied, albuminuria, proteinuria, and hematuria as well as an elevation in blood urea nitrogen and serum creatinine were observed. Additionally CT scan of the kidneys showed a decrease in tissue density suggestive of inflammation and interstitial edema. On the other hand, dialysis patients are a high-risk group than the general population. The current treatment for COVID-19 in acute kidney injury includes supportive management or kidney replacement therapy. All patients need to be quarantined. An N95 fit-tested mask and protective clothing and proper equipment are necessary. Some drugs can be effective to inhibit the outcome of this infection such as lopinavir/ritonavir, remdesvir, Chloroquine phosphate, convalescent plasma, tocilizumab, ACEi/ ARBs (angiotensin-converting enzyme inhibitor/angiotensin receptor blockers), and hrsACE2 (human recombinant soluble angiotensin-converting-enzyme 2).